Horizontal heat flux between urban buildings and soil and its influencing factors - Zhou, Hongxuan; Wang, Xiaolin; Li, Yuanzheng; Han, Fengsen; Hu, Dan (Penerbit Universiti Kebangsaan Malaysia, 2016)
The soil temperature near four external walls with different orientations was investigated in spring and summer. In both seasons, the soil temperature was higher in the positions closest to the buildings, suggesting that the buildings were a heat source for the soil surrounding them. Therefore, it could be confirmed that there was lateral heat transfer between the soil and the buildings. Based on this, a soil heat flux plate was set between the soil and the buildings to investigate the horizontal heat flux. The data showed diurnal variations of the horizontal heat flux in both spring and summer. In order to determine the factors that influenced the horizontal heat flux and to provide a basis to understand its mechanism, the correlations between the data of several meteorological factors and the horizontal heat flux were analysed. The results showed that solar radiation was significantly correlated with the horizontal heat flux (p<0.0001) in any single season and in the two seasons that were studied. Additionally, other meteorological factors (net radiation, air temperature, relative humidity and soil temperature and moisture) showed strong correlations with the horizontal heat flux on a diurnal scale only. On a seasonal time scale, the correlation might be significant (p<0.0001) as well, but the correlation coefficients decreased too significantly, such as those for soil temperature, air temperature and relative humidity. Alternatively, the correlation might not be significant (p>0.05), such as that for soil moisture. The stepwise regression results indicated that the relative importance of these meteorological factors was 48.63, 21.94, 14.44, 8.12 and 6.87% for solar radiation, soil temperature, air temperature, relative humidity and soil moisture, respectively, on a diurnal scale.